Zirconium-Based Ceramic Precursor Material for Polymer Infiltration and Pyrolysis Process, Method for Preparing the Same, and Method for Manufacturing Composite Ceramic Article Using the Same
Patent Information
- Application Number
- KR1020260062029
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-04-14
- Filing Date
- 2026-04-06
- Publication Date
- 2026-10-21
Smart Images

Figure PAT00050_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a zirconium-based ceramic precursor material, a method for manufacturing the same, and a method for manufacturing a composite ceramic molded body using the same. More specifically, the invention relates to a low-viscosity liquid zirconium-based ceramic precursor material comprising a polyzirconium compound, a method for manufacturing the same, and a method for manufacturing a high-density composite ceramic molded body using the same. Background Technology
[0002] With the advancement of the aerospace industry, the demand for materials usable in extreme environments is continuously increasing. In this regard, Ultra-High Temperature Ceramics (UHTCs) are attracting attention as promising candidate materials. In particular, zirconium-based ceramics are receiving attention for their excellent properties, such as high fracture toughness, wear resistance, high melting point, hardness, and heat resistance.
[0003] Zirconia (ZrO2) and zirconium carbide (ZrC) are representative zirconium-based ceramics with high melting points of 2715°C and 3532°C, respectively, which allow them to be used in extreme conditions involving high heat flux. However, due to these high melting points, they have low sinterability, making molding and sintering difficult, which is a limiting factor in their actual applications.
[0004] The Polymer Infiltration and Pyrolysis (PIP) process is one of the well-established methods for densifying and molding ultra-high temperature ceramics. This process involves infiltrating a low-viscosity polymer precursor into a porous matrix and then converting the precursor into a ceramic through high-temperature pyrolysis.
[0005] The PIP process offers the advantages of lower cost, shorter manufacturing time, and deeper penetration depth compared to the Chemical Vapor Infiltration (CVI) process. Additionally, the PIP process generally maintains a thermal decomposition temperature below 1600°C, which is lower than the temperature used in the Reactive Melt Infiltration (RMI) process. Due to these characteristics, the PIP process provides the possibility to manufacture ceramic parts with complex shapes in a near-net-shape.
[0006] However, the PIP process has limitations due to shrinkage and crack formation during thermal decomposition. Therefore, the physical properties of the precursor become a key factor in determining the success of the PIP process.
[0007] Ceramic precursors are generally inorganic polymers containing metal atoms that can be converted into metal carbides, borides, or nitrides at high temperatures. For efficient matrix penetration, the precursor must be primarily in a liquid state or easily soluble in a solvent. For an optimal PIP process, low viscosity to facilitate penetration and high yield after pyrolysis must be satisfied simultaneously.
[0008] Metal carbide precursors can be classified into oxide precursors and non-oxide precursors.
[0009] Non-oxide precursors offer high ceramic yields after pyrolysis by avoiding additional mass loss associated with carbon thermal reduction. However, the high cost of starting materials, demanding reaction conditions, and the risk of explosion due to rapid oxidation limit their widespread application. In contrast, oxide precursors are more industrially applicable due to their ease of handling and lower cost. However, they have the disadvantage of slightly lower yields compared to non-oxide precursors.
[0010] Oxide precursors for zirconium-based ceramics are generally synthesized via a sol-gel reaction using zirconium alkoxides and carbon sources containing hydroxyl groups. However, this method has the following two major problems:
[0011] First, it is difficult to control the extent of the sol-gel reaction, often leading to an excessive increase in molecular weight and the formation of solid precursors. Applying these solid precursors to the PIP process requires additional solvents, which reduces yield and complicates the process. To overcome this, attempts have been made to maintain the precursors in a liquid state using chelating agents; however, optimizing reaction conditions remains challenging due to the varying reactivity of zirconium alkoxides and carbon sources.
[0012] Second, the oxygen content of carbon sources and zirconium sources is high. When manufacturing ZrC, oxygen must be removed through carbon thermal reduction at temperatures above 1500°C. However, the high concentration of hydroxyl groups in the carbon sources increases the carbon demand for oxygen removal, thereby reducing the yield. In addition, there is a risk of matrix damage due to the generation of large amounts of CO2 and CO2 gases.
[0013] Additionally, conventional precursors often have high viscosity, which limits penetration into the matrix during the PIP process. Adding a solvent to address this leads to additional mass loss during the solvent removal process, further reducing the final ceramic yield.
[0014] Therefore, for an efficient PIP process, there is an urgent need to develop new zirconium-based ceramic precursors that simultaneously satisfy low viscosity, liquid state, low oxygen content, and high ceramic yield. The problem to be solved
[0015] The present invention has been devised to solve the problems of the prior art described above. One objective of the present invention is to provide a zirconium-based ceramic precursor material that maintains a liquid state at room temperature while having low viscosity characteristics, can be directly applied to the PIP process without the use of a solvent, and exhibits a high ceramic yield.
[0016] Another objective of the present invention is to provide a method for manufacturing the zirconium-based ceramic precursor material.
[0017] Another objective of the present invention is to provide a method for manufacturing a composite ceramic molded body using the zirconium-based ceramic precursor material. means of solving the problem
[0018] A zirconium-based ceramic precursor material according to an embodiment of the present invention is a precursor material for zirconium carbide, comprising a mixture of a polyzirconium compound of the following chemical formula 1 and an aromatic compound having a vinyl group, and may be in a liquid state at room temperature.
[0019] [Chemical Formula 1]
[0020]
[0021] In the above chemical formula 1, R is a straight-chain or branched alkyl group having about 1 to 6 carbon atoms, and n is an integer from about 1 to 1000.
[0022] In one embodiment, the -OR may be any one selected from the group consisting of an ethoxide group, an n-propoxide group, and an n-butoxide group. For example, the -OR may be an n-propoxide group.
[0023] In one embodiment, the aromatic compound having the vinyl group may include one or more compounds selected from the group consisting of the following chemical formulas 2-1 to 2-4.
[0024] [Chemical Formula 2-1]: Divinylbenzene (DVB)
[0025]
[0026] [Chemical Formula 2-2]: 4-methylstyrene(4-Me)
[0027]
[0028] [Chemical Formula 2-3]: α-methylstyrene(α-Me)
[0029]
[0030] [Chemical Formula 2-4]: Styrene
[0031]
[0032] In one embodiment, the polyzirconium compound and the aromatic compound having a vinyl group may be mixed in a molar ratio of 1:0.5 to 1:3.0.
[0033] A method for manufacturing a zirconium-based ceramic precursor material according to an embodiment of the present invention is a method for manufacturing a precursor material convertible into zirconium carbide, comprising: a first step of hydrolyzing a zirconium alkoxide compound and acrylic acid in a solvent to form an intermediate product; a second step of synthesizing a polyzirconium compound of Formula 1 below by condensing the intermediate product; and a third step of mixing the polyzirconium compound with an aromatic compound having a vinyl group.
[0034] [Chemical Formula 1]
[0035]
[0036] In the above chemical formula 1, R is a straight-chain or branched alkyl group having about 1 to 6 carbon atoms, and n is an integer from about 1 to 1000.
[0037] In one embodiment, the zirconium alkoxide compound may include zirconium propoxide.
[0038] In one embodiment, the zirconium alkoxide compound and the acrylic acid can react in a molar ratio of 1:1.8 to 2.2.
[0039] In one embodiment, in the first step, some of the alkoxide groups of the zirconium alkoxide compound may be substituted with a ligand derived from the acrylic acid.
[0040] In one embodiment, the aromatic compound having the vinyl group may include one or more compounds selected from the group consisting of the following chemical formulas 2-1 to 2-4.
[0041] [Chemical Formula 2-1]: Divinylbenzene (DVB)
[0042]
[0043] [Chemical Formula 2-2]: 4-methylstyrene(4-Me)
[0044]
[0045] [Chemical Formula 2-3]: α-methylstyrene(α-Me)
[0046]
[0047] [Chemical Formula 2-4]: Styrene
[0048]
[0049] In one embodiment, the polyzirconium compound and the aromatic compound having a vinyl group can be mixed in a molar ratio of 1:0.5 to 1:3.0.
[0050] A method for manufacturing a composite ceramic molded body according to an embodiment of the present invention may include: a first step of preparing a porous ceramic molded body; a second step of infiltrating a liquid ceramic precursor material comprising a polyzirconium compound of the following chemical formula 1, an aromatic compound having a vinyl group, and a radical initiator into the pores of the ceramic molded body; a third step of radically crosslinking the polyzirconium compound and the aromatic compound having a vinyl group; and a fourth step of pyrolyzing the crosslinked ceramic precursor material to convert it into zirconium carbide.
[0051] [Chemical Formula 1]
[0052]
[0053] In the above chemical formula 1, R is a straight-chain or branched alkyl group having about 1 to 6 carbon atoms, and n is an integer from about 1 to 1000.
[0054] In one embodiment, the ceramic molded body may be formed of ZrB2, ZrC, or HfC.
[0055] In one embodiment, the aromatic compound having the vinyl group may include one or more compounds selected from the group consisting of the following chemical formulas 2-1 to 2-4.
[0056] [Chemical Formula 2-1]: Divinylbenzene (DVB)
[0057]
[0058] [Chemical Formula 2-2]: 4-methylstyrene(4-Me)
[0059]
[0060] [Chemical Formula 2-3]: α-methylstyrene(α-Me)
[0061]
[0062] [Chemical Formula 2-4]: Styrene
[0063]
[0064] In one embodiment, the crosslinking of the polyzirconium compound and the aromatic compound having vinyl groups can be performed at 70 to 100°C.
[0065] In one embodiment, the thermal decomposition of the cross-linked ceramic precursor material can be performed at a temperature of 550°C or higher and 1400°C or lower. Effects of the invention
[0066] According to the zirconium-based ceramic precursor material, the method for manufacturing the same, and the method for manufacturing a composite ceramic molded body using the same according to an embodiment of the present invention, the ceramic precursor material maintains a liquid state at room temperature and has low viscosity, so excellent penetration can be secured in the PIP process without adding a separate solvent, thereby preventing yield loss due to solvent removal and simplifying the process.
[0067] And, the ceramic precursor material of the present invention is approximately 80 using a radical crosslinking reaction Since complete hardening is possible at a relatively low temperature, it can contribute to improving ceramic yield by suppressing excessive thermal decomposition of organic matter in the stage prior to ceramic conversion.
[0068] In addition, by adjusting the mixing ratio of polyzirconium compound and divinylbenzene, the carbon content of the final ceramic can be easily controlled, allowing for the production of a wide range of C / ZrC composites with various excess carbon contents as well as stoichiometric ZrC. Brief explanation of the drawing
[0069] FIG. 1 is a flowchart illustrating a method for manufacturing a zirconium-based ceramic precursor material according to an embodiment of the present invention. FIG. 2 is a flowchart for explaining a method for manufacturing a composite ceramic molded body according to an embodiment of the present invention. Figure 3 is a diagram illustrating the synthesis strategy of ZrO2 and ZrC precursors. Figure 4 shows the FT-IR spectra of PZC and PZC-DVB before and after crosslinking. Figure 5 shows the XRD diffraction patterns of ZrO2 samples obtained at various temperatures. Figure 6 shows the XRD diffraction patterns of ZrC-DVB with different carbon source contents. Figure 7 shows SEM images of the morphology of the ZrC-DVB sample. Figure 8 shows TEM images of the detailed microstructure morphology and SAED pattern of the ZrC-DVB sample. Figure 9 shows a high-resolution TEM image of ZrC-DVB 3 and the EDS mapping results of ZrC-DVB 0.5. Figure 10 shows the results of TG-DTA thermal analysis to evaluate the mass reduction and endothermic reactions of ZrO2 and ZrC precursors. Figure 11 is a diagram illustrating a process of densifying a ZrB2 molded body with a relative density of 70% using PZC-DVB 0.75 to verify the efficacy of the synthesized precursor in the PIP process. Figure 12 shows the densities of the molded body and composite material measured after each PIP cycle. Figure 13 is the XRD analysis result confirming the change in ceramic composition before and after PIP. Specific details for implementing the invention
[0070] Hereinafter, embodiments of the present invention will be described in detail with reference to the attached drawings. Since the present invention is susceptible to various modifications and may take various forms, specific embodiments are illustrated in the drawings and described in detail in the text. However, this is not intended to limit the present invention to the specific disclosed forms, and it should be understood that it includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the present invention. Similar reference numerals have been used for similar components in the description of each drawing. In the attached drawings, the dimensions of the structures are shown enlarged compared to the actual dimensions for the clarity of the present invention.
[0071] Terms such as "first," "second," etc., may be used to describe various components, but said components should not be limited by said terms. These terms are used solely for the purpose of distinguishing one component from another. For example, without departing from the scope of the present invention, the first component may be named the second component, and similarly, the second component may be named the first component.
[0072] The terms used in this application are used merely to describe specific embodiments and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise. In this application, terms such as "comprising" or "having" are intended to indicate the existence of the features, steps, actions, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the existence or addition of one or more other features, steps, actions, components, parts, or combinations thereof.
[0073] Unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meaning as generally understood by those skilled in the art to which the present invention pertains. Terms such as those defined in commonly used dictionaries should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology, and should not be interpreted in an ideal or overly formal sense unless explicitly defined in this application.
[0075] Zirconium-based ceramic precursor materials
[0076] A zirconium-based ceramic precursor material according to one embodiment of the present invention may include a polyzirconium compound having repeating units of the following chemical formula 1 and an aromatic compound having vinyl groups as a precursor material for zirconium carbide, and may be in a liquid state at room temperature.
[0077] [Chemical Formula 1]
[0078]
[0079] In the above chemical formula 1, R is a straight-chain or branched alkyl group having about 1 to 6 carbon atoms, and n is an integer from about 1 to 1000.
[0080] In the case of the above polyzirconium compound, the central metal zirconium (Zr) atom can bond with multiple oxygen atoms through coordination bonds to form an octahedral or tetrahedral coordination structure.
[0081] In one embodiment, in Formula 1, R represents a straight-chain or branched alkyl group having about 1 to 6 carbon atoms or about 2 to 4 carbon atoms. In one embodiment, R may be selected from the group consisting of ethyl (-C2H5), n-propyl (-C3H7), isopropyl (-CH(CH3)2), n-butyl (-C4H9), sec-butyl (-CH(CH3)C2H5), isobutyl (-CH2CH(CH3)2), tert-butyl (-C(CH3)3), etc. For example, R may be an n-propyl group.
[0082] In one embodiment, in Formula 1, the alkyl group having 1 to 6 carbon atoms may serve to ensure liquid phase stability of the precursor by providing appropriate hydrophobicity and steric hindrance. If the number of carbon atoms is less than 1, steric hindrance may be insufficient, leading to premature gelation, and if the number of carbon atoms is greater than 6, the condensation reaction may be excessively inhibited due to excessive hydrophobicity, resulting in insufficient molecular weight growth.
[0083] In one embodiment, the -OR group is derived from a zirconium alkoxide compound, and some of it is substituted with a carboxyl group during the reaction with acrylic acid, while some remains to form the structure of Formula 1. In one embodiment, the -OR can be selected from the group consisting of an ethoxide group, an n-propoxide group, an n-butoxide group, etc., and preferably, it can be an n-propoxide group.
[0084] In one embodiment, in Formula 1, n is an integer representing the degree of polymerization of the polyzirconium compound. The degree of polymerization n directly affects physical properties such as the molecular weight, viscosity, and ceramic yield of the precursor. In one embodiment, for appropriate viscosity of the polyzirconium compound, the degree of polymerization (n) in Formula 1 may be about 1 to 1000. If the degree of polymerization (n) is less than 1, the molecular weight is excessively low, which may increase volatilization loss during the curing process and reduce the ceramic yield. On the other hand, if the degree of polymerization (n) exceeds 1000, the viscosity increases excessively, which may result in insufficient penetration into the porous matrix during the impregnation step of the PIP process. In one embodiment, the degree of polymerization (n) of the polyzirconium compound may be an integer of about 1 to 500, about 1 to 100, or about 1 to 50.
[0085] In one embodiment, in a polyzirconium compound of Formula 1, a carboxyl group (-COO-) derived from acrylic acid can form a chelation bond with a zirconium atom. Chelation is a phenomenon in which a single ligand binds to a central metal through two or more coordination sites, and is thermodynamically more stable than a simple coordination bond. The chelation effect of the carboxyl group can play a key role in ensuring liquid-phase stability by suppressing excessive hydrolysis and condensation reactions of zirconium alkoxide.
[0086] In one embodiment, the polyzirconium compound of Formula 1 may include a vinyl group (-CH=CH2) derived from acrylic acid. The vinyl group has a carbon-carbon double bond, which can act as a reaction site for radical polymerization. Therefore, in the case of the polyzirconium compound, in the presence of a radical initiator (e.g., AIBN), the vinyl group forms a cross-link through a chain polymerization reaction, which is a key component of the double-crosslinking mechanism of the present invention.
[0087] The aromatic compound having the vinyl group can function as an additional carbon source and solvent. The aromatic compound having the vinyl group is capable of radical curing due to the vinyl group and has high thermal stability due to the inclusion of an aromatic benzene ring. Furthermore, the aromatic compound having the vinyl group may be a liquid organic compound that can be physically mixed with the polyzirconium compound without a chemical reaction at low temperatures. For example, the aromatic compound having the vinyl group may be a liquid organic compound that does not have an oxygen-containing functional group, such as a hydroxyl group (-OH), so that a condensation reaction with the polyzirconium compound does not occur. For example, the aromatic compound having the vinyl group does not contain a hydroxyl group, so it can supply carbon without increasing the oxygen content and simultaneously significantly lower the viscosity of the precursor.
[0088] In one embodiment, the aromatic compound having the vinyl group may include one or more selected from the group consisting of the following chemical formulas 2-1 to 2-4.
[0089] [Chemical Formula 2-1]: Divinylbenzene (DVB)
[0090]
[0091] [Chemical Formula 2-2]: 4-methylstyrene(4-Me)
[0092]
[0093] [Chemical Formula 2-3]: α-methylstyrene(α-Me)
[0094]
[0095] [Chemical Formula 2-4]: Styrene
[0096]
[0098] In one embodiment, the polyzirconium compound and the aromatic compound having vinyl groups may be mixed in a molar ratio of about 1:0.5 to 1:3.0. In this case, the zirconium-based ceramic precursor material may not contain a solvent and may have a viscosity of about 15 to 21 cP upon mixing with the aromatic compound having vinyl groups. If the molar ratio of the polyzirconium compound and the aromatic compound having vinyl groups is less than 1:0.5, a problem may arise in which a large amount of oxygen remains even after the carbon thermal reduction process due to a lack of carbon sources, and if it exceeds 1:3.0, a problem may arise in which an excessive amount of carbon sources is contained, resulting in an excessive amount of carbon remaining after the carbon thermal reduction process. For example, the polyzirconium compound and the aromatic compound having vinyl groups may be mixed in a molar ratio of about 1:0.6 to 1:2.5, or about 1:0.7 to 1:2.0. The carbon content of the final ceramic can be controlled according to the molar ratio. For example, stoichiometric ZrC may be formed at a ratio of 1:0.75, and a C / ZrC composite containing excess carbon may be formed at a higher ratio.
[0099] In one embodiment, the polyzirconium compound and the aromatic compound having a vinyl group each have a vinyl group, so they can be crosslinked to each other through the vinyl group. The vinyl group can be cured by thermal crosslinking at a low temperature (e.g., 60°C to 100°C) in the presence of a radical initiator. This low-temperature curing characteristic can contribute to preventing organic decomposition before ceramic conversion and achieving a high ceramic yield. For example, the polyzirconium compound and the aromatic compound having a vinyl group can be cured by thermal crosslinking at about 80°C after being infiltrated into a ceramic molded body.
[0101] Method for manufacturing zirconium-based ceramic precursor materials
[0102] FIG. 1 is a flowchart illustrating a method for manufacturing a zirconium-based ceramic precursor material according to an embodiment of the present invention.
[0103] Referring to FIG. 1, a method for manufacturing a zirconium-based ceramic precursor material according to an embodiment of the present invention may include: a first step (S110) of hydrolyzing a zirconium alkoxide compound and a carboxylic acid compound having a vinyl group in a solvent to form an intermediate product; a second step (S120) of synthesizing a polyzirconium compound of Formula 1 below by condensing the intermediate product; and a third step (S130) of mixing the polyzirconium compound with an aromatic compound having a vinyl group.
[0104] [Chemical Formula 1]
[0105]
[0106] In the above chemical formula 1, R is a straight-chain or branched alkyl group having about 1 to 6 carbon atoms, and n is an integer from about 1 to 1000.
[0107] In the first step (S110) above, an intermediate product can be formed by hydrolyzing a zirconium alkoxide compound and a carboxylic acid compound having a vinyl group in a solvent.
[0108] In one embodiment, the zirconium alkoxide compound may be represented by the general formula Zr(OR)4, where R may be an alkyl group having about 1 to 10 carbon atoms or about 1 to 6 carbon atoms. In one embodiment, R may be an alkyl group having about 2 to 6 carbon atoms or about 2 to 4 carbon atoms, more preferably an alkyl group having about 3 to 4 carbon atoms. For example, the zirconium alkoxide compound may include zirconium propoxide (Zr(OPr)4). The zirconium propoxide has a higher zirconium content than zirconium butoxide and has the advantage that the reaction byproduct propanol has a lower boiling point than butanol, making it easy to remove.
[0109] In one embodiment, the carboxylic acid compound having a vinyl group may be an α,β-unsaturated carboxylic acid. In one embodiment, the carboxylic acid compound having a vinyl group may be an α,β-unsaturated carboxylic acid having about 3 to 10 carbon atoms, more preferably an α,β-unsaturated carboxylic acid having about 3 to 6 carbon atoms. For example, the carboxylic acid compound having a vinyl group may include one or more selected from acrylic acid, vinylacetic acid, 3-butene acid, 4-pentene acid, 5-heptanoic acid, etc.
[0110] In one embodiment, the carboxylic acid compound having a vinyl group may include acrylic acid (CH2=CH-COOH). The acrylic acid contains both a vinyl group and a carboxyl group, allowing it to function as a chelating agent while also providing polymerization. The carboxyl group of the acrylic acid is effectively coordinated to zirconium to control the sol-gel reaction rate, and the vinyl group of the acrylic acid can participate in a subsequent crosslinking reaction.
[0111] In one embodiment, the zirconium alkoxide compound and the vinyl group-containing carboxylic acid compound may react in a molar ratio of about 1:1.5 to 1:2.5. In this case, some of the plurality of alkoxide groups of the zirconium alkoxide compound may be substituted with ligands derived from the carboxylic acid compound. For example, one to three of the four propoxy groups of Zr(OPr)4 may be substituted with acrylate groups, and the remainder may be maintained as propoxy groups or hydrolyzed to be converted into hydroxyl groups or oxo groups. In one embodiment, the zirconium alkoxide compound and the vinyl group-containing carboxylic acid compound may react in a molar ratio of about 1:1.8 to 1:2.2, more specifically in a molar ratio of about 1:1.9 to 1:2.1.
[0112] In one embodiment, the hydrolysis reaction of the first step may proceed as a non-hydrolytic sol-gel (NHSG). In this case, the reaction rate can be effectively controlled by using an alcohol (e.g., 1-propanol) as a solvent without directly adding water.
[0113] In one embodiment, the hydrolysis reaction may be carried out at a temperature of about 10°C to 100°C. For example, the hydrolysis reaction may be carried out at a temperature of about 15°C to 80°C, more specifically at about 20°C to 60°C. Meanwhile, the hydrolysis reaction may be carried out for about 1 to 48 hours, more specifically at about 12 to 36 hours, and more specifically at about 18 to 30 hours.
[0114] In the second step (S120) above, a polyzirconium compound can be synthesized by condensing the intermediate product.
[0115] In one embodiment, the condensation reaction of the intermediate product is a process of forming a Zr-O-Zr bond through a dehydration reaction between the hydroxyl groups of the intermediate product. Through this, a zirconium oxo cluster or oligomer structure can be formed.
[0116] In one embodiment, when hydrolysis and condensation reactions are performed using zirconium propoxide (Zr(OPr)4) and acrylic acid as the zirconium alkoxide compound and the carboxylic acid compound having a vinyl group, a polyzirconium compound having repeating units of Formula 1 can be synthesized.
[0117] In one embodiment, a process of removing solvent and unreacted material may be additionally performed after the polyzirconium compound is synthesized. This may be carried out by methods such as vacuum evaporation or reduced pressure distillation. For example, after the polyzirconium compound is synthesized, the solvent may be removed under reduced pressure conditions at a temperature of about 60°C to 120°C.
[0118] In one embodiment, the viscosity of the polyzirconium compound obtained through the condensation reaction at 25°C may be in the range of about 300 cP to 800 cP, about 470 cP to 570 cP, or about 500 cP to 540 cP.
[0119] In the third step (S130) above, the aromatic compound having a vinyl group functions as an additional carbon source, which can ultimately enable the production of zirconium carbide (ZrC), zirconium oxide (ZrOC), or a carbon / zirconium carbide complex (C / ZrC). Additionally, since the aromatic compound having a vinyl group does not contain a hydroxyl group, it does not undergo an additional sol-gel reaction with the polyzirconium compound at room temperature, and a uniform liquid precursor can be formed with simple mixing alone.
[0120] In one embodiment, the aromatic compound having the vinyl group may include one or more selected from the group consisting of the following chemical formulas 2-1 to 2-4.
[0121] [Chemical Formula 2-1]: Divinylbenzene (DVB)
[0122]
[0123] [Chemical Formula 2-2]: 4-methylstyrene(4-Me)
[0124]
[0125] [Chemical Formula 2-3]: α-methylstyrene(α-Me)
[0126]
[0127] [Chemical Formula 2-4]: Styrene
[0128]
[0130] In one embodiment, the polyzirconium compound and the aromatic compound having vinyl groups can be mixed in a molar ratio of about 1:0.5 to 1:3.0, more specifically in a molar ratio of about 1:0.6 to 1:2.5, and even more specifically in a molar ratio of about 1:0.7 to 1:2.0. The composition of the final product can be controlled according to the mixing ratio of the polyzirconium compound and the aromatic compound having vinyl groups. For example, when the molar ratio of the polyzirconium compound and the aromatic compound having a vinyl group is about 1:0.5, the final product may contain ZrC and residual ZrO2; when it is about 1:0.75, the final product may contain stoichiometric ZrC; when it is about 1:1.0 to 1:1.5, the final product may contain ZrC and a small amount of excess carbon; and when it is about 1:2.0 to 1:3.0, the final product may be in the form of a composite containing ZrC and a large amount of excess carbon.
[0131] In one embodiment, when the zirconium-based ceramic precursor material is a mixture of the polyzirconium compound and the aromatic compound having vinyl groups, the viscosity of the mixture decreases as the content of the aromatic compound having vinyl groups increases. For example, when the polyzirconium compound and the divinylbenzene compound are mixed in a molar ratio of 1:3.0, the viscosity of the mixture can be lowered to about 18 cP, and excellent penetration can be exhibited in the PIP process.
[0132] According to the zirconium-based ceramic precursor material and the method for manufacturing the same of the present invention, the molecular weight of the polyzirconium compound can be easily controlled by using only a single type of zirconium source, and the reaction rate can be appropriately controlled by acrylic acid acting as a chelating agent.
[0133] In addition, the mixture of the polyzirconium compound and the aromatic compound having a vinyl group remains in a liquid state at room temperature, so the addition of a solvent is unnecessary, and excessive hydrolysis and condensation can be prevented by not directly adding water.
[0134] In addition, the carbon content of the final ceramic can be easily controlled through the mixing ratio of the aromatic compound having the vinyl group, and the ZrO2 precursor and ZrC precursor can be manufactured by the same process.
[0136] Method for manufacturing a composite ceramic molded body
[0137] FIG. 2 is a flowchart for explaining a method for manufacturing a composite ceramic molded body according to an embodiment of the present invention.
[0138] Referring to FIG. 2, a method for manufacturing a composite ceramic molded body according to another embodiment of the present invention may include: a first step (S310) of preparing a porous ceramic molded body; a second step (S320) of infiltrating a liquid ceramic precursor material comprising a polyzirconium compound of Formula 1, an aromatic compound having a vinyl group, and a radical initiator into the pores of the ceramic molded body; a third step (S330) of radically crosslinking the polyzirconium compound and the aromatic compound having a vinyl group; and a fourth step (S340) of pyrolyzing the crosslinked ceramic precursor material to convert it into zirconium carbide.
[0139] [Chemical Formula 1]
[0140]
[0141] In the above chemical formula 1, R is a straight-chain or branched alkyl group having about 1 to 6 carbon atoms, and n is an integer from about 1 to 1000.
[0142] In the first step (S210) above, the porous ceramic molded body is a preform to be densified through a PIP process and includes a plurality of pores. The molded body can be manufactured by compression molding ceramic powder and partial sintering.
[0143] In one embodiment, the porous ceramic molded body may comprise an ultra-high temperature ceramic material, for example, a boride, carbide, nitride of a transition metal, or a mixture thereof. For example, the porous ceramic molded body may comprise one or more selected from ZrB2, HfB2, TiB2, ZrC, HfC, TaC, ZrN, HfN, etc.
[0144] In one embodiment, the relative density of the porous ceramic molded body may be about 50% to 85%, more specifically 60% to 80%, and even more specifically 65% to 75%. This porosity of the ceramic molded body enables effective penetration of the precursor material.
[0145] In the second step (S220) above, a liquid ceramic precursor material can be infiltrated into the pores of the ceramic molded body.
[0146] In one embodiment, when a zirconium carbide phase is to be formed within the pores of the ceramic molded body, the ceramic precursor material may include a polyzirconium compound of Formula 1, an aromatic compound having a vinyl group, and a radical initiator. Since the aromatic compound having a vinyl group also functions as a solvent, there is no need to add a separate solvent in this case.
[0147] The above polyzirconium compound may be manufactured by the aforementioned manufacturing method.
[0148] The aromatic compound having the above vinyl group may include one or more selected from the group consisting of the following chemical formulas 2-1 to 2-4.
[0149] [Chemical Formula 2-1]: Divinylbenzene (DVB)
[0150]
[0151] [Chemical Formula 2-2]: 4-methylstyrene(4-Me)
[0152]
[0153] [Chemical Formula 2-3]: α-methylstyrene(α-Me)
[0154]
[0155] [Chemical Formula 2-4]: Styrene
[0156]
[0157] The radical initiator may be a thermal radical initiator. For example, azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO), di-tert-butyl peroxide, potassium persulfate, etc. may be used as the radical initiator. Preferably, AIBN may be used. The radical initiator may be included in an amount of about 1 to 10 parts by weight, more specifically about 2 to 7 parts by weight, per 100 parts by weight of the polyzirconium compound.
[0158] The infiltration of the above ceramic precursor material can be performed through vacuum infiltration, pressurized infiltration, or a combination thereof.
[0159] In one embodiment, in the case of vacuum penetration, about 10 -3 to 10 -1 It can be performed for 5 to 60 minutes, more specifically 10 to 40 minutes, and even more specifically 15 to 30 minutes, under reduced pressure conditions of atm. In another embodiment, in the case of pressurized penetration, it can be performed for 5 to 60 minutes, more specifically 10 to 40 minutes, and even more specifically 15 to 30 minutes, under pressurized conditions of 2 bar to 10 bar.
[0160] In the above third step (S230), the radical crosslinking can be performed through thermal treatment.
[0161] In one embodiment, the vinyl groups included in the polyzirconium compound and the aromatic compound having vinyl groups can form a three-dimensional cross-linked network by being activated by a radical initiator and bonding to each other. The radical cross-linking can be performed at a temperature of about 60°C to 100°C, specifically about 70°C to 95°C, and more specifically about 75°C to 85°C.
[0162] In one embodiment, the radical crosslinking may be performed under an inert atmosphere. For example, the radical crosslinking may be performed in an inert gas atmosphere such as argon or nitrogen. Meanwhile, the radical crosslinking reaction may be performed for about 6 to 24 hours, more specifically about 8 to 18 hours, and even more specifically about 10 to 14 hours.
[0163] In one embodiment, after the radical crosslinking, the ceramic precursor material hardens from a liquid state to a solid state, and this hardening of the ceramic precursor material to a solid state can prevent the volatilization of low molecular weight substances during the subsequent pyrolysis process and contribute to a high ceramic yield.
[0164] In the above fourth step (S240), the cross-linked ceramic precursor material can be converted into zirconium carbide by thermal decomposition.
[0165] In one embodiment, when the ceramic precursor material is converted into zirconium carbide, the pyrolysis may be performed in an inert or reducing atmosphere. For example, the pyrolysis may be performed under conditions such as argon, nitrogen, or vacuum. In this case, the pyrolysis temperature may be approximately 1400°C to 1900°C, more specifically 1500°C to 1800°C, and even more specifically 1600°C to 1750°C. Since the carbon thermal reduction reaction (ZrO2 + 3C → ZrC + 2CO) is generally completed at 1500°C or higher, it is preferable that the pyrolysis temperature be approximately 1600°C or higher for complete oxygen removal.
[0166] In one embodiment, cubic zirconium carbide (cubic ZrC) can be formed through the pyrolysis. For example, when a ceramic precursor material is applied in which the polyzirconium compound and the DVB are mixed in a molar ratio of 1:0.75, a stoichiometric ZrC phase may be formed, and when a ceramic precursor material is applied in which the polyzirconium compound and the DVB are mixed in a molar ratio of 1:1.0 or higher, a composite phase of ZrC and excess carbon may be formed. Meanwhile, the excess carbon may form an amorphous or turbostratic carbon layer around the ZrC particles, which may contribute to inhibiting ZrC particle growth and maintaining the nanocrystalline structure.
[0167] Meanwhile, to manufacture the above composite ceramic molded body, the cycle consisting of the second to fourth steps can be repeated about 1 to 10 times, more specifically about 2 to 7 times, and even more specifically about 3 to 5 times, and the density of the molded body may increase as the number of repetitions of the cycle increases.
[0168] A composite ceramic molded body manufactured according to the present invention may have a high relative density of about 75% to 99%, more specifically about 80% to 98%, and may have a low porosity of about 1% to 20%, and ZrC or ZrOC may be uniformly distributed within the pores of the molded body, and as a result, may have excellent mechanical properties of high hardness and fracture toughness.
[0170] Specific embodiments of the present invention are described in detail below. However, the following embodiments are merely partial embodiments of the present invention, and the scope of the present invention is not limited to the following embodiments.
[0172] [Example 1]
[0173] Synthesis of PZC (Polyzirconium compound)
[0174] PZC, a zirconia precursor, was synthesized in a 100 mL three-necked flask equipped with a magnetic stirrer. Specifically, 0.01 mol of Zr(OPr)4 and 0.02 mol of acrylic acid were placed in the flask in air at room temperature and reacted by stirring at 500 rpm for 24 hours. After the reaction, the resulting white solution was heated to 85°C using a vacuum evaporator to remove the solvent and unreacted materials. Finally, PZC was obtained as a yellow viscous liquid.
[0176] Manufacturing of ZrO2
[0177] First, 0.15 g of AIBN was dissolved in methylene chloride (MC) to prepare a homogeneous solution. Then, 6 g of PZC was added to this clear solution and mixed vigorously. The mixture was placed in an alumina crucible, transferred to a tubular furnace, and subjected to a radical crosslinking reaction at 80°C for 12 hours under an argon atmosphere. After curing, crosslinked PZC, a brittle solid with a bright yellow color, was obtained. This powder was ground with an agate mortar and pestle, and then thermally decomposed under an air stream at 500°C, 600°C, 700°C, and 800°C to produce ZrO2. The white ZrO2 powders obtained at different temperatures were named ZrO2-500, ZrO2-600, ZrO2-700, and ZrO2-800, respectively (Table 1).
[0178] Sample Precursor Pyrolysis temperature(°C) Condition ZrO2-500 PZC 500 Air ZrO2-600 PZC 600 ZrO2-700 PZC 700 ZrO2-800 PZC 800
[0180] [Example 2-1]
[0181] Synthesis of PZC-DVB
[0182] PZC-DVB, used as a ZrC precursor, was prepared by mixing PZC and DVB (divinyl benzene) in various ratios. The mixing ratios of PZC and DVB are shown in Table 2, and the mixtures are labeled from PZC-DVB 0.5 to PZC-DVB 3, reflecting the ratio of DVB.
[0183] Sample Ratio Viscosity[cP] Zr(OPr)4 DVB PZC 1 1502 PZC-DVB 0.5 1 0.5 1012 PZC-DVB 0.75 1 0.75 517.2 PZC-DVB 1 1 1 310.3 PZC-DVB 1.5 1 1.5 155 PZC-DVB 2 1 2 79.4 PZC-DVB 2.5 1 2.5 23.2 PZC-DVB 3 1 3 18.0
[0185] Preparation of ZrC-DVB
[0186] For the synthesis of ZrC, 0.15 g of azobisisobutyronitrile (AIBN) was directly dissolved in 6 g of PZC-DVB. This mixture was placed in a tubular furnace equipped with a carbon crucible, and a radical crosslinking reaction was carried out at 80°C for 12 hours under an argon atmosphere. At this stage, a hard, deep yellow solid of crosslinked PZC-DVB was produced. This solid was ground with an agate mortar, and the resulting powder was pyrolyzed in an improved Spark Plasma Sintering (SPS) apparatus under vacuum at 1700°C for 2 hours at a heating rate of 50°C / min to produce zirconium carbide. Generally, 1600 Since it was important to remove all oxygen from the precursor through the carbon-thermal reduction reaction occurring above, the reaction temperature was set to 1700°C to ensure the formation of ZrC. Through this process, black ZrC samples with various carbon element ratios (hereinafter referred to as 'ZrC-DVB') were obtained. The synthesized ZrC was named ZrC-DVB, and was designated from ZrC-DVB 0.5 to ZrC-DVB 3 depending on the DVB content. The synthesis conditions for all ZrC-DVBs are summarized in Table 3.
[0187] Sample Precursor Pyrolysis temperature(°C) Condition ZrC-DVB 0.5 PZC-DVB 0.5 1700 Vacuum ZrC-DVB 0.75 PZC-DVB 0.75 1700 ZrC-DVB 1 PZC-DVB 1 1700 ZrC-DVB 1.5 PZC-DVB 1.5 1700 ZrC-DVB 2 PZC-DVB 2 1700 ZrC-DVB 2.5 PZC-DVB 2.5 1700 ZrC-DVB 3 PZC-DVB 3 1700
[0189] Preparation of ZrB2-ZrC composites via PIP (Polymer infiltration and pyrolysis) using ZrC precursors
[0190] After drying the 68 vol% ZrB2 slurry, 10 mm ZrB2 pellets were prepared by heating at 1900°C under vacuum at a heating rate of 50°C / min for 1 hour. The ZrB2 pellets were placed in a graphite mold, and 0.75 PZC-DVB was poured in to completely submerge the pellets. Subsequently, the graphite mold was placed in a metal container, and 10 -2 Vacuum penetration was carried out by vacuuming at an atm for 20 minutes. Subsequently, high-pressure argon gas (5 bar) was injected for 20 minutes to further promote precursor penetration.
[0191] After the infiltration treatment, the ZrB2 sample infiltrated with the precursor was cured at 80°C for 12 hours in an argon atmosphere, and then pyrolyzed at 1700°C in a vacuum for 2 hours at a heating rate of 50°C / min using an improved SPS device.
[0192] The above process was repeated three times to obtain a ZrB2-ZrC composite sample.
[0194] [Example 2-2]
[0195] PZC-4-Me, used as a ZrC precursor, was prepared by mixing PZC and 4-methylstyrene in various ratios.
[0196] ZrC-4-Me and ZrB2-ZrC composites were prepared using the above ZrC precursor in the same manner as in Example 2-1.
[0198] [Examples 2-3]
[0199] PZC-α-Me, used as a ZrC precursor, was prepared by mixing PZC and α-methylstyrene in various ratios.
[0200] ZrC-4-Me and ZrB2-ZrC composites were prepared using the above ZrC precursor in the same manner as in Example 2-1.
[0202] [Examples 2-4]
[0203] PZC-styrene, used as a ZrC precursor, was prepared by mixing PZC and styrene in various ratios.
[0204] ZrC-4-Me and ZrB2-ZrC composites were prepared using the above ZrC precursor in the same manner as in Example 2-1.
[0206] [Experimental Example]
[0207] Figure 3 is a diagram illustrating the synthesis strategy of ZrO2 and ZrC precursors.
[0208] Referring to FIG. 3, the reason Zr(OPr)4 was selected as the Zr raw material instead of zirconium butoxide (Zr(OBu)4) is that Zr(OPr)4 has a higher Zr content, and propanol, a byproduct of the sol-gel reaction using Zr(OPr)4, has a lower boiling point than butanol produced from Zr(OBu)4, making it easier to remove. Considering the rapid reaction rate of Zr(OPr)4, it is essential to maintain the precursor in a liquid state by controlling its molecular weight for potential applications in the PIP process, and to achieve this, the sol-gel reaction must be intentionally controlled to proceed incompletely. Therefore, in the present invention, liquid ZrO2 and ZrC precursors were synthesized using the following three synthesis strategies.
[0209] (I) In the sol-gel reaction, only Zr(OPr)4 was reacted without adding a carbon source containing a hydroxyl group. This is because when two or more reactants are reacted, it is difficult to control the molecular weight of the product because the reaction rates of each reactant are different.
[0210] (II) A non-hydrolyzed sol-gel (NHSG) was used to reduce the reaction rate. This is because the hydrolysis and condensation rates are significantly accelerated in the hydrolyzed sol-gel (HSG) system due to the presence of water. Here, propanol acted as both a solvent and a hydrolysis byproduct, effectively reducing the reaction rate.
[0211] (III) In addition, a chelating agent is required to block the reaction site of Zr(OPr)4. Most chelating agents contain two adjacent oxygen atoms within the molecule to form a coordinate bond with Zr. Among them, carboxylic acids possess functional groups that can be utilized not only as chelating agents but also as initiators for the sol-gel reaction. Therefore, acrylic acid, which contains both vinyl and carbonyl groups, was used as the chelating agent. Due to the vinyl group, acrylic acid can be used to some extent in organic solvents, and the carboxylic acid within the molecule can effectively induce the sol-gel reaction of Zr(OPr)4 at an appropriate rate even in the absence of water.
[0212] After the reaction, unreacted materials in the propanol and PZC were rapidly removed using a vacuum evaporator. The synthesized PZC was a viscous, dark yellow liquid with a viscosity of 1500 cP. Finally, this liquid PZC was used as a ZrO2 precursor.
[0213] To prepare ZrC precursors, DVB was added to PZC to provide an additional carbon source. Table 2 shows the ratios of the Zr source and DVB; PZC-DVB is labeled from 0.5 to 3, reflecting the ratio of Zr(OPr)⁴ to DVB. Table 2 also shows the viscosity of these mixtures. Notably, the viscosity of PZC-DVB decreases as the amount of DVB increases. This decrease in viscosity is due to the fact that DVB lacks hydroxyl groups, so it does not react with PZC at room temperature and forms a simple mixture with low viscosity. When the ratio of DVB reached three times the Zr source, the viscosity decreased to 18 cP. The low viscosity of PZC-DVB allows the precursor to easily penetrate into the matrix during the PIP process. Therefore, PZC-DVB was adopted as a ZrC precursor for the PIP process.
[0215] Generally, ultra-high temperature ceramics such as SiC, ZrC, and ZrB2 require sintering temperatures of 1,500°C or higher. However, most inorganic polymers used as ceramic precursors decompose at temperatures above 500°C. Therefore, to prevent the volatilization of low-molecular-weight polymers and the consequent reduction in ceramic yield, it is important to increase the molecular weight through a curing process prior to thermal decomposition. While oxide precursors are typically cured by increasing the sol-gel reactivity at temperatures above 150°C, the present invention utilizes chain polymerization via vinyl groups. PZC and PZC-DVB precursors containing vinyl groups derived from acrylic acid and DVB can undergo crosslinking reactions via thermal initiators such as AIBN. Consequently, the precursors of the present invention can be cured at 80°C through a thermal crosslinking reaction using AIBN. (See Figs. 3c and 3d)
[0216] Figure 4 shows the FT-IR spectra of PZC and PZC-DVB before and after crosslinking.
[0217] Referring to FIG. 4a and c, 2924cm -1 Wow, 2861cm -1 Two absorption peaks are observed, which represent the CH stretching vibration. 1121 cm⁻¹ -1 The peak is attributed to the CO stretching vibration, and at 646 cm⁻¹ -1 Wow, 1548cm -1 The peaks correspond to the Zr-O bond and the Zr-OC bond, respectively.
[0218] Additionally, referring to Fig. 4b, the stretching vibration of the CH bond within the phenyl group of DVB is 3100-3000 cm⁻¹ -1 It appears in [location]. The absorption peak positions of PZC and PZC-DVB are consistent with the expected molecular structure. In particular, the FT-IR spectra of PZC and PZC-DVB show 1728 cm⁻¹, which corresponds to the C=O bond vibration of acrylic acid. -1 The 1644 cm⁻¹ peak, as well as the C=C bond vibrations present in acrylic acid -1A peak also appeared. This indicates that acrylic acid acts effectively as a chelating agent to suppress excessive reaction in the sol-gel process of Zr(OPr)4. Meanwhile, referring to Figures 4b and 4d, 1644 cm⁻¹ -1 It can be confirmed that the peak corresponding to the vinyl group located at [location] disappeared after curing, which indicates that the thermal crosslinking of PZC and PZC-DVB by AIBN was successfully achieved. Additionally, after curing, 1624 cm⁻¹ -1 The enhancement of the CC aromatic stretching mode is consistent with previous research results on polystyrene and polydivinylbenzene.
[0220] Figure 5 shows the XRD diffraction patterns of ZrO2 samples obtained at various temperatures.
[0221] Referring to Fig. 5, most XRD patterns showed sharp peaks indicating crystalline material, whereas ZrO2-500 showed broad peaks suggesting an amorphous component (see Fig. 5a). This implies that 500°C is insufficient for the precursor to be completely converted into ZrO2. All XRD patterns of ZrO2 are consistent with the tetragonal structure (t-ZrO2, JCPDS card number 01-080-0965), except for small peaks around 28° and 32° of ZrO2-800. These peaks indicate that monoclinic ZrO2 (m-ZrO2, JCPDS card number 01-078-0047) was formed at 800°C. Previous studies have reported that the phase transition from t-ZrO2 to m-ZrO2 at high temperatures is accompanied by a large volume change. If a phase transition occurs within the matrix during the PIP process, defects may occur in the composite material due to the aforementioned volume change. Therefore, when a phase stabilizer such as Y2O3 is not used, the appropriate thermal decomposition temperature of the PZC precursor in the PIP process was set to 600–700°C in air.
[0223] Figure 6 shows the XRD diffraction patterns of ZrC-DVB with different carbon source contents.
[0224] Referring to Figure 6, all samples except ZrC-DVB 0.5 correspond to the cubic ZrC structure (JCPDS card number 98-061-9173). In the case of ZrC-DVB 0.5, a small peak representing m-ZrO2 was observed at 28°, suggesting that there was insufficient carbon source in ZrC-DVB 0.5 for oxygen to be completely removed during the carbon-thermal reduction process.
[0225] In addition, the average ZrC particle size of ZrC-DVB was calculated using the FWHM value and the Scherrer equation, and the results are shown in Figure 6h. The ZrC particle sizes of ZrC-DVB 0.5 and ZrC-DVB 0.75 were 54 nm and 82 nm, respectively, because residual ZrO2 generated during the carbon thermal reduction process exists between ZrC particles and inhibits particle growth. For ZrC-DVB-0.75, ZrC-DVB-1, and ZrC-DVB-1.5, the particle size was consistently measured to be approximately 83 nm, with minimal variation. This is because at this stage, the excess carbon is not sufficient to affect the ZrC particle size. However, in the case of ZrC-DVB 2, which has an increased excess carbon content, the excess carbon surrounding the ZrC in an amorphous form inhibited the growth of the ZrC particle size, resulting in a decrease in particle size to 40 nm. In the case of ZrC-DVB-2.5 and ZrC-DVB-3, which had much higher excess carbon content, aggregates of excess carbon began to transform into a layered structure, and the average particle size increased. Unfortunately, in the remaining samples, crystal peaks of excess carbon were not distinguished in X-ray diffraction analysis, but it was confirmed that pure cubic ZrC was formed. This is presumed to be because the graphitization peaks formed by excess carbon during the ZrC synthesis process become prominent when sintered at temperatures above 1800°C.
[0227] The exact excess carbon content of ZrC-DVB was measured through ICP-OES and elemental analysis, and Table 4 summarizes the atomic content of C, H, O, N, and Zr of each ZrC-DVB sample.
[0228] Sample ICP-OES Elemental analysis ZrC x Zirconium Carbon Nitrogen Hydrogen ZrC-DVB 0.5 86.48 9.21 0.05 - Uncertainty ZrC-DVB 0.75 87.72 12.06 0.06 0.02 ZrC 1.06 ZrC-DVB 1 86.27 13.18 - 0.02 ZrC 1.21 ZrC-DVB 1.5 80.58 18.25 - - ZrC 1.83 ZrC-DVB 2 77.22 22.31 - 0.04 ZrC 2.24 ZrC-DVB 2.5 73.76 26.10 - 0.01 ZrC 2.7 ZrC-DVB 3 73.29 26.21 - 0.02 ZrC 2.91
[0229] Referring to Table 4, as expected, the Zr content measured by ICP-OES decreased as the carbon source increased. However, an exceptional phenomenon was observed where the Zr content was lower in ZrC-DVB 0.5 than in ZrC-DVB 0.75, suggesting that residual ZrO2 exists in ZrC-DVB 0.5 after carbon-thermal reduction due to a lack of DVB. This is because in ZrO2, two oxygen atoms reduce the mass fraction of Zr, whereas in ZrC, only one carbon atom plays this role.
[0230] Elemental analysis results showed that the carbon content increased from DVB-ZrC 0.5 to DVB-ZrC 3, while N and H showed negligiblely low content (<0.1%). The oxygen content of ZrC-DVB 0.5 could not be measured due to strong Zr-O bonding at the operating temperature used. Table 4 shows that ZrC-DVB samples, excluding ZrC-DVB 0.5, consist of ZrC and excess carbon, and that ZrC-DVB 0.75 exhibits a nearly stoichiometric ZrC composition.
[0232] Figure 7 shows SEM images of the morphology of the ZrC-DVB sample.
[0233] Referring to Fig. 7, ZrC particles were observed from ZrC-DVB 0.5 to ZrC-DVB 1.5 (see Fig. 7 a–f). Small white particles were observed in ZrC-DVB 0.5, which represent residual ZrO2 particles after carbon thermal reduction. In ZrC-DVB 1.5–3 (see Fig. 7 g–n), the area of the black phase representing excess carbon increased as the amount of carbon source increased.
[0235] Figure 8 shows TEM images of the detailed microstructure morphology and SAED pattern of the ZrC-DVB sample.
[0236] Referring to Figures 8a through d, the morphology of each particle of ZrC-DVB 0.5, ZrC-DVB 0.75, ZrC-DVB 1, and ZrC-DVB 1.5 was observed to be an aggregated ZrC matrix with a similar shape. However, interestingly, in the morphologies of ZrC-DVB 2, ZrC-DVB 2.5, and ZrC-DVB 3 (see Figures 8e through g), the carbon source is dispersed throughout the ZrC matrix. This is in contrast to the morphology of ZrC-DVB, which has a low excess carbon content. It is presumed that when the carbon content within the ZrC matrix exceeds a certain amount, the carbon layer acts as a barrier surrounding the ZrC, inhibiting the growth of the ZrC particles, which is consistent with the XRD results.
[0238] Figure 9 shows a high-resolution TEM image of ZrC-DVB 3 and the EDS mapping results of ZrC-DVB 0.5.
[0239] Referring to Fig. 9a, high-resolution TEM analysis of ZrC-DVB 3 clearly showed that a carbon layer formed around the ZrC particles. A well-defined single-crystal lattice with a spacing of 0.27 nm corresponds to the ZrC
[0111] plane. The surrounding layer has a spacing of 0.34 nm, which matches the interplanar distance of turbostratic carbon. This suggests that excess carbon was encapsulated and formed around the ZrC.
[0240] Referring to Fig. 9b, the EDS mapping results of ZrC-DVB 0.5 showed an oxygen concentration of 4.5 at%. Oxygen is uniformly distributed in ZrC-DVB 0.5, indicating the formation of Zr-OC. This result clearly demonstrates that the amount of DVB contained in ZrC-DVB 0.5 is insufficient to complete carbon-thermal reduction. The high carbon content compared to the elemental analysis results is due to the influence of the carbon-composed TEM grid.
[0241] In summary, these analyses confirm that crystalline C / ZrC ceramics were produced through the effective pyrolysis of ZrC precursors. ZrC-DVB 0.75 derived from PZC-DVB 0.75 is nearly stoichiometric ZrC with no excess carbon. If the amount of carbon source in the precursor is less than the amount contained in PZC-DVB 0.75, some oxygen remains in the resulting ZrC powder; conversely, if the content of the carbon source exceeds the amount contained in PZC-DVB 0.75, excess carbon is produced. In particular, since PZC-DVB is simply a mixture of PZC and DVB without a sol-gel reaction, the content of the carbon source in the precursor can be freely controlled. In other words, the oxygen and carbon concentrations of the final ZrC can be easily controlled.
[0243] Figure 10 shows the results of TG-DTA thermal analysis to evaluate the mass reduction and endothermic reactions of ZrO2 and ZrC precursors.
[0244] Figure 10a shows the TG-DTA thermal analysis curve of PZC heated in air from 40°C to 600°C at a heating rate of 10°C / min. As the precursor temperature increased to 450°C, mass loss occurred due to three main causes. Specifically, the first is mass loss due to the decomposition and removal of unreacted molecules such as propanol; the second is mass loss due to the decomposition of organic materials within PZC by oxidation at high temperatures; and the third is mass loss due to the condensation of hydroxyl groups (OH)4 as the sol-gel reaction proceeds, forming Zr-O bonds and simultaneously releasing water molecules.
[0245] Above 430°C, all organic molecules stabilizing the Zr(OH)4 clusters were removed, and ZrO2 was formed in a tetragonal state with a regular crystal structure. Above 550°C, no further weight loss was observed, indicating that a thermal decomposition temperature of 600°C is sufficient for producing ZrO2, which is consistent with the XRD results (see Fig. 5b). The final ceramic yield of the ZrO2 precursor was 47%.
[0246] Figure 10b shows the TGA thermal analysis curve of PZC-DVB 0.75 with a Zr-to-C ratio of 1:1, intended to investigate the thermal properties of the ZrC precursor. PZC-DVB 0.75 was heated to 1700°C at a rate of 10°C / min under an Ar atmosphere. The numerous vinyl groups present in DVB promoted strong thermal crosslinking, resulting in a mass loss of less than 2% up to 380°C. The DTA graph showed that initial decomposition occurred between 380°C and 510°C, suggesting that the organic polymeric backbone of divinylbenzene decomposed and was converted into inorganic carbon. The greatest weight loss during the initial decomposition occurred at approximately 420°C, resulting in a residual weight of 59%. Subsequently, the weight remained stable up to 1300°C, except for a minor loss of about 2% due to phase changes. Above 1300°C, a secondary mass loss reaction induced by carbon-thermal reduction occurred. The greatest weight loss at this stage was observed at 1490°C, which is consistent with the previously reported ZrC formation temperature via carbonthermal reduction. After carbonthermal reduction was completed at 1600°C, no further mass loss was observed up to 1700°C. The final ceramic yield of ZrC-DVB 0.75 was 38%, which is significantly higher than that of other oxide precursors. In several prior studies, the TGA temperature was limited to 1400°C due to equipment constraints, preventing the carbonthermal reduction reaction from proceeding fully. In this invention, the ceramic yield reached 55% at 1400°C, achieving a very high yield compared to other previously reported ZrC oxide precursors. Generally, the organic carbon source of ZrC oxide precursors possesses two or more hydroxyl functional groups, which bind strongly to the Zr source to prevent decomposition and removal below the carbonthermal reduction temperature. However, DVB contains vinyl groups instead of hydroxyl groups, enabling thermal cross-linking with PZC.Therefore, due to its low oxygen content, PZC-DVB requires less oxygen and carbon to be removed during the carbon thermal reduction process compared to other oxide precursors. Additionally, the low viscosity of PZC-DVB eliminates the need for additional solvents during the infiltration process, thereby preventing ceramic yield loss caused by solvent removal in the PIP process.
[0248] Figure 11 is a diagram illustrating a process for densifying a ZrB2 molded body with a relative density of 70% using PZC-DVB 0.75 to verify the efficacy of the synthesized precursor in the PIP process, and Figure 12 shows the densities of the molded body and the composite measured after each PIP cycle. In the process illustrated in Figure 11, three consecutive PIP cycles were performed using PZC-DVB 0.75 without adding a solvent.
[0249] Referring to Figures 11 and 12, the ZrB2-ZrC composite was successfully prepared and exhibited a darker color compared to pure ZrB2. The density of the molded body was 4.28 g / cm3 and increased to 4.51 g / cm3 after 3 PIP cycles.
[0251] Figure 13 is the XRD analysis result confirming the change in ceramic composition before and after PIP.
[0252] Referring to Fig. 13, a pure ZrB2 peak initially appeared in the green material (see Fig. 13a), but a ZrC peak also appeared after three PIP processes (see Fig. 13b). This indicates that ZrC was successfully incorporated into the ZrB2 matrix. This result clearly demonstrates the effect of the ZrC precursor in the PIP process.
[0254] Figure 14 shows the results of measuring the viscosity of ZrC precursors according to the mixing ratio of PZC and each of the four carbon sources [(a) Styrene monomer, (b) 4-methylstyrene, (c) α-methylstyrene, (d) Divinylbenzene].
[0255] Referring to Fig. 14, when each of the four carbon sources was individually mixed with PZC and the miscibility was evaluated, a single, uniform liquid phase was maintained at room temperature in all cases, and no noticeable phase separation was observed. This phenomenon is because none of the four carbon sources have hydroxyl groups, so a condensation reaction with PZC does not occur, and in the absence of an initiator, chain polymerization between vinyl groups does not proceed at room temperature. These results demonstrate that all four carbon sources exhibit stable mixing behavior with PZC and are therefore suitable as carbon donors for PZC-based ZrC precursors.
[0256] Next, the effect of the carbon source mixing ratio on the viscosity of the precursor was evaluated. For efficient penetration into the porous matrix during the PIP process, the rheological properties of the precursor are very important, and low viscosity is particularly desirable. Pure PZC exhibited a relatively high viscosity of 690.2 cP, but for all carbon sources, the viscosity of the precursor gradually decreased as the carbon source content increased. In particular, when 3 equivalents of a carbon source were added relative to PZC, the viscosity dropped to less than 20 cP in all compositions. These results demonstrate that all four carbon sources used in this invention effectively lower the viscosity of PZC while simultaneously acting as carbon donors and solvents. Consequently, the developed ZrC precursor can maintain a low-viscosity liquid state without additional solvent, which is highly advantageous for the PIP process. Through a more detailed comparison, 4MS exhibited the lowest viscosity at the same mixing ratio, followed by αMS, DVB, and SM in descending order of viscosity. Nevertheless, the differences between the four systems were not significant, and all compositions fit well within the low viscosity range required for the actual application of the PIP process.
[0258] Figures 15 and 16 show XRD patterns and SEM images of ZrC after pyrolysis according to the type and content of the carbon source.
[0259] Referring to Fig. 15, diffraction peaks corresponding to the (111), (200), (220), (311), (222), and (400) planes of ZrC were detected in all compositions, clearly confirming the formation of the cubic ZrC phase. These results demonstrate that, regardless of the chemical composition of a specific carbon source, ZrC ceramics can be consistently obtained by mixing the selected carbon source with PZC, followed by curing and subsequent pyrolysis. This suggests that the cross-linking network formed through vinyl-vinyl chain polymerization remains sufficiently intact up to the ceramicization temperature, acting as an effective carbon reservoir, and thus allows for the stable conversion of PZC-based precursors into ZrC. Crystallographic analysis revealed a distinct peak shift attributed to residual carbon in the α-methylstyrene system with a carbon / PZC ratio of 3.0. This suggests the formation of an unstable cubic ZrC phase, implying that structural stability during the ceramicization process is lower compared to other carbon sources.
[0260] Referring to Fig. 16, the microstructure of the pyrolyzed ZrC ceramics was analyzed by SEM, and a generally continuous ZrC matrix was observed in all cases. However, in the case of low carbon content (0.5 ratio), relatively bright ZrO2 particles were locally present within the ZrC matrix, indicating that incomplete carbon-thermal reduction occurred under carbon-deficient conditions. On the other hand, in the case of high carbon content (3.0 ratio), a distinct dark region corresponding to excess free carbon appeared, suggesting that more carbon than the stoichiometric ratio was supplied during the ceramicization process.
[0261] The effect of carbon source content on the final Zr:C ratio of ZrC ceramics was investigated by systematically varying the carbon content of the ZrC precursor. SEM analysis revealed that as the carbon source content increased up to 3.0, the proportion of the ZrO2 phase, which exhibits a bright white contrast, gradually decreased. At these high carbon contents, residual graphite was also observed, appearing as a shell-like carbon-rich region surrounding the ZrC matrix. Conversely, at low carbon source contents, additional bright surface phases were detected, which are presumed to be Zr-OC and ZrO2. This is likely related to incomplete or unstable cross-linking and subsequent thermal decomposition. In particular, for all compositions with a carbon source ratio of 0.5, the carbon content was insufficient to fully carry out carbon-thermal reduction, and SEM analysis confirmed the presence of Zr-OC and / or ZrO2 phases instead of the fully converted ZrC phase.
[0262] ICP-OES analysis was performed to determine whether the Zr:C ratio in the final ZrC ceramic could be controlled by controlling the carbon source content, and the results are shown in Table 5.
[0263] Sample ICP-OES data Sample ICP-OES data Zirconium (wt%) Zirconium (wt%) SM 0.5 80.05 MS 0.5 79.03 SM 1.0 81.89 MS 1.0 76.22 SM 2.0 80.24 MS 2.0 80.8 SM 3.0 78.21 MS 3.0 83.09 4ms 0.5 82.79 DVB 0.5 74.63 4MS 1.0 82.01 DVB 0.5 70.56 4MS 2.0 76.48 DVB 0.5 67.18 4MS 3.0 77.20 DVB 0.5 64.97
[0264] Referring to Table 5, the overall trend shows that the Zr content decreases as the carbon source content increases. In particular, for the DVB-based system, the Zr content was approximately 74% when the carbon / PZC ratio was 0.5, and it decreased monotonically as the DVB content increased, which is consistent with the gradual increase in excess carbon within the ZrC phase. On the other hand, for the 4MS, αMS, and SM-based systems, the Zr content did not systematically decrease as the carbon source ratio increased. This deviation can be explained by two factors. First, when the carbon content is low, the amount of available carbon is insufficient, preventing the complete consumption of oxygen through carbon-thermal reduction and leaving residual Zr-O containing species. Second, unlike DVB, which contains two vinyl groups per molecule and can achieve a relatively high crosslinking density upon curing, 4MS, αMS, and SM each contain only one vinyl group. Consequently, the crosslinking density is low, leading to incomplete carbon-thermal reduction and promoting the formation of Zr-OC and ZrO2 phases. The presence of these oxygen-containing zirconium phases increases the effective zirconium fraction, thereby hindering the ideal foreclosure reduction of Zr content with increasing carbon source content. Collectively, these results demonstrate that among the four carbon sources investigated, DVB is the most suitable for precisely controlling the carbon content of ZrC after heat treatment due to its high functionality, enhanced crosslinking efficiency, and more complete carbon thermal conversion.
[0266] Figure 17 shows the TGA curve of a ZrC precursor containing four carbon sources with a carbon / PZC ratio of 1.0.
[0267] Referring to Fig. 17, the samples were heated to 1700 °C at a rate of 10 °C / min in an argon atmosphere, allowing for the direct observation of the pyrolysis and decomposition stages of the ZrC precursors. Due to the application of a vinyl-based crosslinking step, initial mass loss was relatively small in all four systems, indicating that the organic network was effectively stabilized prior to high-temperature treatment. Nevertheless, differences were observed in the starting point and magnitude of the initial decomposition, which can be attributed to differences in the degree of hardening and crosslinking density between the different carbon sources. A second mass loss phenomenon occurred in all compositions above approximately 1300 °C, corresponding to carbon-thermal reduction and ZrC formation. The starting temperature of the secondary mass loss coincides with previously reported ZrC formation temperatures, confirming that the designed precursors undergo the expected carbon-thermal conversion pathway. The final ceramic yield determined from the residual mass at 1700 °C ranged from 28.5% to 38.5%, with the DVB-based precursor exhibiting the highest yield. This result is consistent with the fact that the higher vinyl functional group content of DVB compared to other carbon sources enables a higher crosslinking density during the curing process, which consequently reduces volatile losses and leads to more efficient carbon thermal reduction. This interpretation is also in line with the previously discussed ICP-OES data, which also indicates more complete conversion and a better-controlled Zr:C ratio in the DVB-containing system.
[0269] Figure 18 is a graph showing the change in density of the composite material measured after each PIP cycle using different precursors, and Figure 19 is an XRD pattern analyzing the change in composition of the ceramic phase before and after PIP.
[0270] Referring to Fig. 18, among the four systems, the density increase rate was greatest when using a DVB-based precursor (△ρ 0.22), this indicated the most efficient pore filling and matrix densification.
[0271] Referring to Fig. 19, only the ZrB2 diffraction peak was observed in the initial molded body, but after three PIP cycles, an additional peak corresponding to ZrC was clearly observed. This confirms that the ZrC precursor was effectively infiltrated and converted within the ZrB2 matrix. Therefore, it can be seen that the ZrC precursor synthesized in the present invention effectively functions as a PIP raw material for matrix densification. Furthermore, as a result of comparing the peak intensities of the XRD patterns, the DVB-based system exhibited the highest ZrC content in the final composite, which is consistent with excellent densification characteristics.
[0273] The present invention focused on identifying the most suitable carbon source for the preparation of ZrC precursors to be used in the PIP process. ZrC precursors were synthesized by mixing PZC, obtained through the sol-gel reaction of propoxyrkonium and acrylic acid, with various carbon sources. To ensure applicability for PIP densification, the four selected carbon sources were aromatic compounds that (i) possess a thermally stable benzene ring, (ii) contain vinyl groups capable of radical crosslinking, and (iii) do not contain oxygen-containing functional groups such as hydroxyl (-OH) groups. Although all four carbon sources produced ZrC ceramics after pyrolysis, subtle differences in behavior and performance were observed due to structural differences among the carbon sources.
[0274] (1) From a practical and economic perspective, a large amount of precursor is generally required for effective densification in the PIP process. Considering precursor scalability and cost, which are important factors for potential commercialization, styrene is the most economical choice, and DVB, αMS, and 4MS are the most economical in order of estimated cost and procurement difficulty.
[0275] (2). In the investigated composition range, all four carbon sources were completely mixed with PZC to form a homogeneous solution without phase separation. Additionally, the viscosity of the precursors gradually decreased as the carbon source content increased. At a given equivalence ratio, the lowest viscosity was obtained from 4MS, followed by αMS, DVB, and styrene. However, the viscosity difference between the four systems was not significant, and all compositions were within a low viscosity range suitable for PIP application without additional solvent.
[0276] (3) When comparing the structural stability of the generated ZrC precursors, the vinyl-based crosslinking mechanism was found to be an important factor. In systems such as styrene, particularly α-methylstyrene, evidence of incomplete reaction was observed in both the SEM microstructure and XRD patterns because the curing mechanism is structurally unfavorable for efficient crosslinking. After pyrolysis, these systems often showed residual carbon and / or ZrO₂, which implies incomplete ceramicization and an unstable final microstructure.
[0277] (4) In terms of ceramic yield during direct ceramicization, DVB-based precursors showed the highest residual mass. Carbon sources with less effective or unstable hardening behavior exhibited lower ceramic yields, which highlights the correlation between crosslinking efficiency, carbon thermal conversion, and the final performance of the ceramic.
[0278] (5) Finally, when the PIP efficiency was directly compared by infiltrating the ZrC precursor into the ZrB₂ molded body, DVB again exhibited the most favorable behavior. Consistent with the structural and thermal analysis results, the DVB-based system provided the greatest increase in composite density and the most stable ZrC formation within the ZrB₂ matrix.
[0279] Overall, while all four carbon sources can, in principle, be used to generate ZrC via the PZC-based precursor route, DVB was identified as the most promising among the reviewed carbon sources as it offers the most favorable combination of crosslinking efficiency, ceramic yield, phase stability, and PIP densification performance.
[0281] Although the present invention has been described above with reference to preferred embodiments, those skilled in the art will understand that various modifications and changes can be made to the invention without departing from the spirit and scope of the invention as set forth in the following claims. Explanation of the symbols
[0282] doesn't exist
Claims
Claim 1 A zirconium-based ceramic precursor material comprising a mixture of a polyzirconium compound of the following Chemical Formula 1 and an aromatic compound having a vinyl group, as a precursor material for zirconium carbide, and being in a liquid state at room temperature: [Chemical Formula 1] In the above chemical formula 1, R is a straight-chain or branched alkyl group having about 1 to 6 carbon atoms, and n is an integer from about 1 to 1000. Claim 2 A zirconium-based ceramic precursor material according to claim 1, wherein the -OR is selected from the group consisting of an ethoxide group, an n-propoxide group, and an n-butoxide group. Claim 3 A zirconium-based ceramic precursor material according to claim 2, characterized in that the -OR is an n-propoxide group. Claim 4 Zirconium-based ceramic precursor material according to claim 1, characterized in that the aromatic compound having a vinyl group comprises one or more compounds selected from the group consisting of the following chemical formulas 2-1 to 2-4: [Chemical Formula 2-1]: Divinylbenzene (DVB) [Chemical Formula 2-2]: 4-methylstyrene(4-Me) [Chemical Formula 2-3]: α-methylstyrene(α-Me) [Chemical Formula 2-4]: Styrene Claim 5 A zirconium-based ceramic precursor material according to claim 4, characterized in that the polyzirconium compound and the aromatic compound having a vinyl group are mixed in a molar ratio of 1:0.5 to 1:3.
0. Claim 6 A method for preparing a precursor material convertible into zirconium carbide, comprising: a first step of hydrolyzing a zirconium alkoxide compound and acrylic acid in a solvent to form an intermediate product; a second step of condensing the intermediate product to synthesize a polyzirconium compound of Formula 1 below; and a third step of mixing the polyzirconium compound with an aromatic compound having a vinyl group; [Formula 1] In the above chemical formula 1, R is a straight-chain or branched alkyl group having about 1 to 6 carbon atoms, and n is an integer from about 1 to 1000. Claim 7 A method for manufacturing a zirconium-based ceramic precursor material according to claim 6, wherein the zirconium alkoxide compound comprises zirconium propoxide. Claim 8 A method for manufacturing a zirconium-based ceramic precursor material according to claim 6, characterized in that the zirconium alkoxide compound and the acrylic acid react in a molar ratio of 1:1.8 to 2.
2. Claim 9 A method for manufacturing a zirconium-based ceramic precursor material according to claim 8, wherein, in the first step, some of the alkoxide groups of the zirconium alkoxide compound are substituted with a ligand derived from the acrylic acid. Claim 10 A method for preparing a zirconium-based ceramic precursor material according to claim 6, wherein the aromatic compound having a vinyl group comprises one or more compounds selected from the group consisting of the following chemical formulas 2-1 to 2-4: [Chemical Formula 2-1]: Divinylbenzene (DVB) [Chemical Formula 2-2]: 4-methylstyrene(4-Me) [Chemical Formula 2-3]: α-methylstyrene(α-Me) [Chemical Formula 2-4]: Styrene Claim 11 A method for manufacturing a zirconium-based ceramic precursor material according to claim 10, characterized by mixing the polyzirconium compound and the aromatic compound having a vinyl group in a molar ratio of 1:0.5 to 1:3.
0. Claim 12 A method for manufacturing a composite ceramic molded body, comprising: a first step of preparing a porous ceramic molded body; a second step of infiltrating a liquid ceramic precursor material comprising a polyzirconium compound of Formula 1, an aromatic compound having a vinyl group, and a radical initiator into the pores of the ceramic molded body; a third step of radically crosslinking the polyzirconium compound and the aromatic compound having a vinyl group; and a fourth step of thermally decomposing the crosslinked ceramic precursor material to convert it into zirconium carbide; [Formula 1] In the above chemical formula 1, R is a straight-chain or branched alkyl group having about 1 to 6 carbon atoms, and n is an integer from about 1 to 1000. Claim 13 A method for manufacturing a composite ceramic molded body according to claim 12, wherein the ceramic molded body is formed of ZrB2, ZrC, or HfC. Claim 14 A method for manufacturing a composite ceramic molded body according to claim 12, wherein the aromatic compound having a vinyl group comprises one or more compounds selected from the group consisting of the following chemical formulas 2-1 to 2-4: [Chemical Formula 2-1]: Divinylbenzene (DVB) [Chemical Formula 2-2]: 4-methylstyrene(4-Me) [Chemical Formula 2-3]: α-methylstyrene(α-Me) [Chemical Formula 2-4]: Styrene Claim 15 A method for manufacturing a composite ceramic molded body according to claim 14, characterized in that the crosslinking of the polyzirconium compound and the aromatic compound having vinyl groups is performed at 70 to 100°C. Claim 16 A method for manufacturing a composite ceramic molded body according to claim 12, characterized in that the thermal decomposition of the cross-linked ceramic precursor material is performed at a temperature of 550°C or higher and 1400°C or lower.